The Influence of the Amount of ZIS Fund Receipt, Company Size on Company Performance with CSR as a Moderation Variable in Sharia Commercial Banks in Indonesia - Agung, Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sharia Commercial Banks in Indonesia have a social role by Law No. 21 of 2008 which has the task of collecting Zakat, Infaq, Alms, and Waqf funds from the community. This research is to test whether this role, if implemented by Sharia Commercial Banks as one of the company's core operational business activities, can improve the Performance of Sharia Commercial Banks, determined by ROA which measures profitability. with CSR initiatives acting as a moderating factor and business size as another independent variable. The study results show that receipt of ZIS funds from the public and internal banks has a positive impact on company performance. Apart from that, what is detrimental to company performance is the size of its assets. CSR moderates ZIS negatively on company performance, while the results of CSR moderation on the size of company assets have a positive impact on business performance.